ANALISIS EVALUASI PENATAUSAHAAN BARANG MILIK DAERAH - Randalayuk, Christina; Asnawi, Meinarni; Wijaya, Anthonius H. Citra (Jurnal Akuntansi, Audit, dan Aset, 2019)
The objectives of this study were to evaluate the management of Government Fixed Assets inPegunungan Bintang Regency. The analysis technique used in this study was descriptive analysis.The paper described the Analysis of Regional Property Administration Evaluation in thePegunungan Bintang District Government. The data was shown in tables with numbers andpercentages to be analyzed further with descriptive analysis. In analyzing research data the authoruses qualitative descriptive analysis, also known as content analysis.The results of the study showed that the administration of regional fixed assets in terms of recordingthe assets, The Financial and Asset Management Agency (BPKAD) in Pegunungan BintangRegency has carried out the bookkeeping. This comprises of process of recording regional fixedassets in lists of its users, the inventory cards, and in the database of regional’s fixed assets. Beforerecording the assets, at first, Asset have been identified into its classification based on the type andcodes of regional fixed assets. Thus, in general, it can be concluded that the implementation ofaccounting in the administration of fixed assets in The Financial and Asset Management Agency ofPegunungan Bintang Regency has been well implemented. Evaluation of administration of regionalfixed assets to the inventory on The Financial and Asset Management Agency in PegununganBintang Regency has been carried out in accordance with mandated regulations. This can be seenfrom the evidence of inventory execution such as the existence of recording documents, theDatabase of Inventory, and documented in Inventories Books. In addition, there are reportingdocuments such as List of Inventory Recapitulation and List of inventory Mutations. Evaluation ofadministration of regional fixed assets in terms of reporting to The Financial and AssetManagement Agency in Pegunungan Bintang Regency is carried out in stages based on informationcontained in the list of assets keepers and a list of the authority of its users and keepers. Authoritiesof fixed assets users have to submit assets User Reports every semester, yearly, and 5 years toassets keepers.